Pengembangan Budaya Organisasi Bisnis Berbasis E-Comers Di Pimpinan Cabang Pemuda Muhammadiyah Dan Pimpinan Cabang Nasyiatul Aisyiyah Medan Baru - Riyan Pradesyah; AL Bara (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2021)
The development of information technology is currently experiencing increased renewal, the renewal of information technology can make it easier for people to carry out daily activities. One of the technological developments that touch people's lives is buying and selling. At this time buying and selling touches the point of very sophisticated technology, where buying and selling which is usually done must meet face-to-face, can now be done digitally or not face-to-face. The purpose of this activity is to provide training to strengthen E-Comers-Based Business Organizations at the Muhammadiyah Youth Branch Manager and the Nasyiatul Aisyiyah Branch Manager in Medan Baru, by utilizing technology and internet networks. Partners in the service carried out were the Muhammadiyah Youth Branch Manager and the Nasyiatul Aisyiyah Medan Baru Branch Manager, while the number of participants in the activities carried out was 45 people. The method of implementing this activity is carried out through several stages, including the delivery of material on e-commerce and financing, then followed by training to register products to the market place. Based on the results of the service carried out, that there are still many who do not understand or know how to sell products in the marketplace. From the results of the service carried out, now the new Muhammadiyah and Nasyiatul Aisyiyah Medan Youth Branch Managers can register their business products in the market place, so that their products are widely known by the public, and easy to find.